2021
DOI: 10.1049/rpg2.12141
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state model of DFIG‐based wind power plant for load flow analysis

Abstract: The steady‐state models of electric power system components are crucial for the analysis of system load flow or preliminary study of the system stability. At present, penetration of wind power plant (WPP) in power system continues to increase, and its modelling development and investigation is also still a very active research area. This paper proposes a simple technique for modelling doubly fed induction generator (DFIG)‐based WPP to be used in power system steady‐state (i.e. load flow) studies. In the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 22 publications
0
33
0
7
Order By: Relevance
“…It can be shown that a solution to the load flow problem of a power system can be found by solving the following bus or nodal equations [12]:…”
Section: Dslf Problem Formulationmentioning
confidence: 99%
“…It can be shown that a solution to the load flow problem of a power system can be found by solving the following bus or nodal equations [12]:…”
Section: Dslf Problem Formulationmentioning
confidence: 99%
“…In recent years, many investigations have been conducted in the context of modeling and integrating WTGS into steady state load flow analysis of an electric power system. For example, references [3]- [21] propose interesting methods to incorporate WTGS into load flow analysis. In [3]- [5], the induction generator equivalent circuit of the WTGS is converted to a three-node model.…”
Section: Introductionmentioning
confidence: 99%
“…The model in [15], [16] is derived using Kirchhoff and Ohm laws. In [17]- [21], DFIG-based variable speed WTGS models for steady state load flow analysis have been proposed. Equivalent circuits of the doubly fed induction generator (DFIG) have also been used in developing the models in [17]- [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of WPP steady state load flow model, several interesting techniques have been proposed. References [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], for example, report some of the recent methods. In [7][8][9], multiple-node models of asynchronous generator-based WPP for load flow analysis are proposed.…”
Section: Introductionmentioning
confidence: 99%